Gambaran Pengetahuan dan Motivasi Remaja tentang Kesehatan Reproduksi di SMP Pertiwi 1 Kota Jambi - Hesty, Hesty; Maimaznah, Maimaznah; Hidayat, Muhammad (Prosiding Seminar Kesehatan Nasional, 2024)
Reproductive health is important in the lives of individuals and communities. According to WHO, reproductive health includes efforts to maintain and improve the physical, mental, and social well-being of individuals at all stages of life related to the reproductive system. Factors that influence reproductive health include social, economic, cultural, and environmental. This study aims to determine the description of adolescent knowledge and motivation about reproductive health at SMP Pertiwi 1, Jambi City and is a quantitative study with a descriptive analytical design. The study was conducted from September 2023 to August 2024. The number of samples was 65 respondents using the proportional random sampling technique. Data collection by filling out questionnaires was analyzed univariately. The results obtained based on age characteristics are at the age of 13 years as many as 27 respondents (41.5%), the characteristics of respondents based on the most classes are in class 8 totaling 27 (41.54%) and the majority of female gender 59 respondents (90.8%), for good knowledge 30 respondents (46.15%), sufficient knowledge 20 respondents (30.77%), lack of knowledge 15 respondents (23.08%) for good motivation 34 respondents (52.31%) moderate motivation 18 respondents (27.69%) and lack of motivation 13 (20%). It can be concluded that most respondents have good knowledge 46.15% and for good motivation 52.31%. It is hoped that the school will continue to work with various teams that can provide education and motivate their students to always carry out reproductive health care